2017
DOI: 10.1007/s11764-017-0659-3
|View full text |Cite
|
Sign up to set email alerts
|

Bright light therapy improves cancer-related fatigue in cancer survivors: a randomized controlled trial

Abstract: These findings, along with previous reports of light therapy for CRF, support the use of this intervention to improve fatigue in cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 30 publications
2
67
3
Order By: Relevance
“…For example, anti‐cytokine therapies may be beneficial for patients with elevated inflammation, although concerns about adverse effects limit the use of these agents in patients with cancer. Pharmacologic agents also could be used to target neurotransmitter, neuro‐immune, and other systems related to fatigue (eg, buproprion, minocycline), whereas bright‐light therapy could target circadian rhythm disturbance . Of note, given the multidimensional nature of fatigue, interventions that influence multiple systems may be most effective.…”
Section: Summary and Implications For Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, anti‐cytokine therapies may be beneficial for patients with elevated inflammation, although concerns about adverse effects limit the use of these agents in patients with cancer. Pharmacologic agents also could be used to target neurotransmitter, neuro‐immune, and other systems related to fatigue (eg, buproprion, minocycline), whereas bright‐light therapy could target circadian rhythm disturbance . Of note, given the multidimensional nature of fatigue, interventions that influence multiple systems may be most effective.…”
Section: Summary and Implications For Interventionmentioning
confidence: 99%
“…Pharmacologic agents also could be used to target neurotransmitter, neuro-immune, and other systems related to fatigue (eg, buproprion, minocycline), whereas bright-light therapy could target circadian rhythm disturbance. 124 Of note, given the multidimensional nature of fatigue, interventions that influence multiple systems may be most effective. Indeed, psychosocial, exercise, and mind-body interventions appear to be more beneficial for CRF than pharmacotherapy, 82 perhaps because these approaches have effects on a range of biobehavioral processes relevant for fatigue.…”
Section: Summary and Implications For Interventionmentioning
confidence: 99%
“…Studies specifically intervening on circadian rhythms that take into account the 24-h activity rhythm remain scarce. A number of studies have reported reduced circadian disruption after bright light therapy in patients with dementia [80], Parkinson's disease [81], depression [82], cardiovascular disease [83], and cancer [84]. However, it is largely unknown to what extent intervening on circadian factors and, subsequently 24-h activity rhythms, improves relevant clinical outcomes such as disease progression or mortality.…”
Section: Research Agendamentioning
confidence: 99%
“…Early morning bright light therapy has been shown to protect against this disruption, which may also serve to protect against cancer‐related fatigue (Ancoli‐Israel et al., ; Neikrug et al., ). These findings have been replicated in patients with other types of cancer besides breast cancer (Johnson et al., ; Wu et al., ).…”
Section: Chronotherapymentioning
confidence: 75%